Heteroatom-doped carbon networks enabling robust and flexible silicon anodes for high energy Li-ion batteries. Issue 35 (28th August 2020) - Shao, Rong; Zhu, Feng; Cao, Zhenjiang; Zhang, Zhengping; Dou, Meiling; Niu, Jin; Zhu, Baoning; Wang, Feng
Abstract : Flexible Si anodes for Li-ion batteries were enabled by heteroatom-doped carbon networks, the mechanisms by which heteroatom-doped carbons enhance the Si anodes performance were detailed explored and provided. Abstract : Fabricating a silicon–carbon (Si/C) hybrid material is a powerful strategy to enhance the Li-ion storage capacity of Si-based anodes. However, because additional binders and conductive agents need to be incorporated in the final anodes, the resulting Si/C materials generally have poor areal capacities, limiting their practical applications. In addition, the heteroatom effects of carbon modifiers on anode performance and the modification mechanism still need to be explored. In an attempt to overcome these limitations, we have prepared flexible Si/C anodes by an efficient method using commercial Si nanoparticles and three polymers as precursors. By simple slurry coating followed by low-temperature pyrolysis, the resulting polymer-derived carbons with different heteroatom dopants form continuous conductive networks and simultaneously anchor Si nanoparticles on copper foil, affording Si/C anodes with good performance. Material characterization, electrochemical tests and first-principles calculations show that N doping facilitates charge transfer and ion diffusion within Si/C anodes. More importantly, N, O co-doping improves the mechanical strength of Si/C anodes via double-interface bonding, thus efficiently accommodating the volume expansion of Si/C anodes. As a result, a Si/C anode prepared using a chitosan precursor (Si@CTSC) exhibits the best half-cell performance among all the anodes tested. Moreover, the Si@CTSC anode can be used to assemble a pouch cell with a LiCoO2 cathode, which shows an ultrahigh energy density of up to 540 W h kg −1 (based on the total weight of the electrode materials) and good bending flexibility, increasing the possibility of practical applications of Si/C anodes in advanced Li-ion batteries.